Restoring the tallgrass prairie : an illustrated manual for Iowa and the upper Midwest - Shirley, Shirley (Bur oak original., 1994)
"Iowa is the only state that lies entirely within the natural region of the tallgrass prairie. Early documents indicate that 95 percent of the state - close to 30 million acres - was covered by prairie vegetation at the time of Euro-American settlement. By 1930 the prairie sod had been almost totally converted to cropland; only about 30,000 acres of the original "great green sea" remained. Now, in this gracefully illustrated manual, Shirley Shirley has created a step-by-step guide to reconstructing the natural landscape of Iowa and the Upper Midwest."--Publisher